Approach to identifying research gaps on vector-borne and other infectious diseases of poverty in urban settings: scoping review protocol from the VERDAS consortium and reflections on the project's implementation - Stéphanie Degroote; Clara Bermudez-Tamayo; Valéry Ridde (BMC, 2018)
Abstract Background This paper presents the overall approach undertaken by the "VEctor boRne DiseAses Scoping reviews" (VERDAS) consortium in response to a call issued by the Vectors, Environment and Society unit of the Special Programme for Research and Training in Tropical Diseases hosted by the World Health Organization. The aim of the project was to undertake a broad knowledge synthesis and identify knowledge gaps regarding the control and prevention of vector-borne diseases in urban settings. Methods The consortium consists of 14 researchers, 13 research assistants, and one research coordinator from seven different institutions in Canada, Colombia, Brazil, France, Spain, and Burkina Faso. A six-step protocol was developed for the scoping reviews undertaken by the consortium, based on the framework developed by Arksey and O'Malley and improved by Levac et al. In the first step, six topics were identified through an international eDelphi consultation. In the next four steps, the scoping reviews were conducted. The sixth step was the VERDAS workshop held in Colombia in March 2017. Discussion In this article, we discuss several methodological issues encountered and share our reflections on this work. We believe this protocol provides a strong example of an exhaustive and rigorous process for performing broad knowledge synthesis for any given topic and should be considered for future research initiatives and donor agendas in multiple fields to highlight research needs scientifically.